Cerâmica com lodo de indústria de placa de circuito impresso, lama vermelha de tratamento de bauxita e escória siderúrgica - Guidolin, Marília Alarcon (2017)
The use of industrial waste in the production of materials can mitigate the impacts generated by the generating agent. The use in civil construction of materials generated from waste, would also minimize the impacts generated by the extraction of natural resources for this sector. The industrial waste used in this research is classified as hazardous waste and the research is based on the hypothesis that it is possible to produce a ceramic material for use in civil construction from printed circuit board industry sludge, bauxite red processing sludge and steel slag, ceramic compositions using these residues as raw material were produced. The sample were made with 20g in mold 20x60 mm and with uniaxial press 5 MPa. The sample were sintered at temperatures of 800, 900, 1000, 1050, 1100 and 1150°C for 6 hours. Moisture tests were carried out, density, granulometry, loss on ignition, XRF, XRD, SEM/EDS, linear firing shrinkage, water absorption, flexural strength and leaching in order to characterize the materials and the ceramic material developed. The results show that there has been fusion of the components of the raw materials. The composition showed the best result achieved flexural strength 5.48 MPa, 4.57% of linear firing decrease, 2.06 density and 19.94% water absorption. The results of the leaching test indicate that the ceramic material after sintering presents traces of Pb, having immobilized only part of the analyzed heavy metals present in the composition of the test specimens, which classifies it as hazardous waste. In comparison with the Brazilian standards, the water absorption and resistance aspects met the requirements for use in ceramic blocks for structural masonry and in categories A, B and C of solid bricks common for masonry, respectively, however, the immobilization of metals is required to achieve an inert ceramic material.